Access to emergency contraception among adolescent girls in Lesotho - Ngwena, Charles (University of Pretoria, 2017)
The study was motivated by studies which have revealed that teenage pregnancy, maternal mortality and unsafe abortion are high in Lesotho. The purpose of the study was to examine whether or not lack of access to emergency contraception as one of the essential forms of contraception could be the reason for the aforementioned health challenges facing adolescent girls in Lesotho. The study was a desktop review with content analysis of documents applicable to the health of adolescents and those relating to access to family planning services for adolescent girls. The woman question was used as a tool for ascertaining whether the health rights of adolescent girls are fulfilled by Lesotho. The legal framework relevant to access to emergency contraception was also scrutinised to ascertain whether they are compliant with human rights treaties ratified by Lesotho. The study is also a comparative analysis of Lesotho's policy frame with South Africa. From the analysis of the literature review, the study uncovered how religious, cultural practices and some areas of the laws relevant to access to emergency contraception for adolescents were not responsive to the female adolescent question, thereby perpetuating infringement of various human rights belonging to adolescent girls. The study also revealed that lack of political will and poor coordination and monitoring of policies, budgetary deficiencies and shortages in human resources are some of the factors inhibiting adolescent's realisation of their full access to family planning services. The study made recommendations which the Government of Lesotho could use to change the current state of access of adolescent girls to emergency contraception.